Meromorphic Solutions of Some Algebraic Differential Equations - Jianming Lin; Weiling Xiong; Wenjun Yuan (Abstract and Applied Analysis)
By means of the normal family theory, we estimate the growth order of meromorphic solutions of some algebraic differential equations and improve the related results of Barsegian et al. (2002). We also give some examples to show that our results occur in some special cases.